Plantas de cobertura em áreas de produção de soja no verão e silagem de milho no inverno, com aplicação de água residuária de suinocultura - Melo, Dirceu de (2016)
System of intensive agricultural production, adopted by most producers, has brought problems to the no tillage system, especially in areas of silage of entire corn plant production. Physical and chemical properties of soil can be changed when soil management has not been properly done. In this context, this study aimed to monitor changes in physical and chemical properties of soil, in field and laboratory, under cover crops associated with swine wastewater application (SWW), in areas used to prepare the whole corn plant silage under no tillage system. The study was conducted on a farm in Matelândia municipality, western Paraná, in a DYSTROPHIC RED Eutroferric soil with 585 g kg-1 clay, 175 g kg-1 silt and 240 g kg-1 sand. The experimental area consisted of seven soil management systems: soybeans, silage, black oats and turnips (SSAN); soybeans, black oats and turnips (SAN); soybeans, silage, scarified with black oats and turnips (SSEAN); soybeans, silage and brachiaria (SSB); soybeans, black oats and silage (SSA); soybean silage (SS); corn and soybeans (SM), repeated for two consecutive years. The treatments received 100 m3 ha-1 years-1 SWW which were separated in two equal doses to be applied: one dose was applied over the corn crop and the another was applied over the cover crops. The experimental design is a completely randomized design (CRD) in a 2 x 7 factorial (with and without SWW application x seven management systems), with four replications per treatment. The results were submitted to the Scott-Knott test at 5% probability. SWW application increased soybeans, as well as fresh and dry mass yield of cover crops; management systems interfered on physical properties of soil and the system that did use cover crops showed the best mechanical resistance to penetration; soil layer with the highest penetration resistance was 0.05 to 0.20 m; scarifying improved physical properties of soil, but they did not change the evaluated crops yield. SWW application did not change physical properties of soil, but there was some phosphorus accumulation on 0-0.1 m layer, as well as acidification trended to occur on soil and there was a saturation decrease by the bases. The SWW application at a dose of 100 m3 ha-1 year-1, under experimental conditions, can be used, although phosphorus and soil acidity must be monitored. Based on these conditions, as long as they use cover crops, it is unnecessary soil tillage. The management system with soybeans in the summer and silage of the whole corn plant in the winter, with cover crops as black oats, is considered the best one.